SHM_415191_HST_3D Limhamn Stone Axe - Qallaki, Ylber; Strandberg, Caroline; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a Mesolithic Limhamn stone axe collected from Nättraby parish in Blekinge in 1895 and currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=693

Link to Sök I Samlingarna

https://samlingar.shm.se/object/C26CC9BC-3467-4095-925E-7317D95967B6
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; History and archaeology; Archaeology/history; Dynamic Collections; Nättraby; Swedish Mesolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi